cAMP Content in Mitochondria of Cardiomyocytes in C57bl/6 Mice With B16/F10 Melanoma in the Background of Chronic Neuropathic Pain - E. M. Frantsiyants; V. A. Bandovkina; I. V. Neskubina; A. I. Shikhlyarova; I. V. Kaplieva; E. I. Surikova; Yu. A. Pogorelova; N. D. Cheryarina; L. K. Trepitaki; S. S. Todorov; N. D. Ushakova; O. G. Ishonina (Фундаментальная и клиническая медицина)
Aim. To study the effect of malignant tumor growth on level of cAMP in mitochondria of cardiomyocytes in mice with chronic neuropathic pain.Materials and Methods. С57ВL/6 mice (n = 336) have been grouped as follows: intact mice (♂n = 21; ♀n = 21), mice with chronic neuropathic pain (♂n = 21; ♀n = 21), mice with melanoma В16/F10 (♂n=63; ♀n=63), and mice with melanoma В16/ F10 and chronic neuropathic pain (♂n=63; ♀n=63). After 1, 2, and 3 weeks of the melanoma growth, cardiac mitochondria of abovementioned mice have been isolated by the centrifugation with the following measurement of cAMP.Results. Chronic neuropathic pain has induced a 3.6-fold reduction in cAMP in cardiac mitochondria of female mice. In mice with melanoma В16/ F10, cardiac cAMP showed 4-fold average increase from the 2nd week of the tumor growth, while in mice with melanoma В16/F10 and chronic neuropathic pain a 2-4-fold increase in cAMP was recorded as soon as from the 1st week of tumor growth, eventually leading to the depletion of cAMP by the 3rd week of the experiment. Serum cAMP concentration did not correlate with the cAMP level in cardiac mitochondria and was reduced in both males and females.Conclusion. Alterations in cAMP concentration in cardiac mitochondria were gender-specific, as female mice responded to a chronic neuropathic pain without other triggers. In mice with melanoma and chronic neuropathic pain, cAMP level raised significantly earlier than in mice without chronic neuropathic pain, resulting in full cAMP depletion by the 3rd week of the experiment.